2023
DOI: 10.3389/fgene.2023.1044555
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry: How researchers use it and what they mean by it

Abstract: Background: Ancestry is often viewed as a more objective and less objectionable population descriptor than race or ethnicity. Perhaps reflecting this, usage of the term “ancestry” is rapidly growing in genetics research, with ancestry groups referenced in many situations. The appropriate usage of population descriptors in genetics research is an ongoing source of debate. Sound normative guidance should rest on an empirical understanding of current usage; in the case of ancestry, questions about how researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…First, by neglecting to distinguish between self-identified racial categories and assigned or assumed racial categories. Second, by the haphazard use and reporting of racial/ethnic variables in genetic research, that is, reliance on race without clearly articulating exactly what race represents ( Yudell et al, 2016 ; Dauda et al, 2023 ). These oversights risk not only perpetuating a misperception of race as genetically based, but, by misclassifying race, may also reduce the validity and reliability of the scientific research.…”
Section: Shortcomings In the Use Of Race In Epigenetic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…First, by neglecting to distinguish between self-identified racial categories and assigned or assumed racial categories. Second, by the haphazard use and reporting of racial/ethnic variables in genetic research, that is, reliance on race without clearly articulating exactly what race represents ( Yudell et al, 2016 ; Dauda et al, 2023 ). These oversights risk not only perpetuating a misperception of race as genetically based, but, by misclassifying race, may also reduce the validity and reliability of the scientific research.…”
Section: Shortcomings In the Use Of Race In Epigenetic Researchmentioning
confidence: 99%
“…Analyses that include genomic sequencing to categorize individuals into ethnic or ancestral groupings are also faced with the limitations of discretizing a continuous and very complex variable ( Lewis et al, 2022 ). Ways in which ancestry data has been used in research shows that it is largely ambiguous and varies across studies, indicating that the field lacks consistent use and definitions of ancestry terms and interpretations ( Dauda et al, 2023 ). The field of epigenetics should continue to conduct empirical studies on the role of genetics in epigenomics.…”
Section: Introductionmentioning
confidence: 99%
“…Today, as we have said, the “populations” that result from this sample inclusion‐and‐exclusion practice are often called “genetic ancestries.” 61 As others have noted, 62 continental‐level genetic ancestry, especially, is imperfect as a proxy for genetic similarity. It is also problematic because these populations do not reliably map onto, yet they are easily and erroneously conflated with, social groupings such as race and ethnicity.…”
Section: Part 3: Polygenic Indexes: General Principles and Applicatio...mentioning
confidence: 99%
“…When using a genetic ancestry concept, it is important both to say that this is neither race nor ethnicity and to affirmatively specify what genetic similarity is and how it is being operationalized in the study. A recent investigation found that scientists use “genetic ancestry” in a variety of ways, including in ways they themselves cannot fully articulate or explain; while some of them view ancestry as closely related to genetics, others view it as only tangentially related 155 . For instance, researchers might explain that their high‐level goal (for scientific reasons they explain) was to include people in their study who were relatively genetically similar to one another and to exclude those who exceeded some threshold of dissimilarity, that one way of thinking about genetic similarity is the time since two people shared a common genetic ancestor, and that they operationalized that by using participants’ report that all four biological grandparents hailed from the same continent (or did not).…”
Section: Part 7: Responsible Behavior In the Context Of Sbg Researchmentioning
confidence: 99%
“…In addition, we believe that the use of the categories “African American” and “European American” mixes both self-identified race and the genetic ancestry construct of ‘European American.’ This introduces ambiguity and confusion in the population descriptors and could inappropriately imply categorical differences, when genetic differences are in fact gradual or clinal ( 4 ). In the discussion, the authors claim that it is “important to confirm and measure ethnicity information from samples using genetic ancestry informative marker data.” ( 1 ) The delineation between ancestry, genetic ancestry, and genetic similarity is complicated but important to state clearly ( 4 , 6 ). Neither “race” nor “ethnicity” can be confirmed or measured by so called ‘ancestry informative markers,’ ( 6 ) and the use of continental ancestry designations is not consistent with modern understanding of genetic variation in humans.…”
mentioning
confidence: 99%